1970
DOI: 10.3329/bjar.v34i1.5750
|View full text |Cite
|
Sign up to set email alerts
|

Varietal performance of transplant <i>aman</i> rice under different hill densities

Abstract: An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from July to December 2004 to evaluate the effect of hill spacing on the performance of BRRI dhan40 and BRRI dhan41 as Transplant aman crop. The experiment consisted of five hill spacings viz., 5cm. 10cm, 15 cm, and 25 cm where row to row spacing of 25 cm was kept constant for all treatments. The experiment was laid out in randomized complete block design with four replications. The 25 cm x 5 cm hill sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
13
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 2 publications
9
13
0
10
Order By: Relevance
“…The response of difference in producing bearing tillers hill -1 might be due to the variation in genetic makeup of the variety. The above results of variability in effective tillers hill -1 are also in full agreement with many workers (Sohel et al, 2009;Hossain et al, 2005;Shrirame and Muley, 2003). The differential response of tillering in the varieties could be attributed due to its genetic potentiality.…”
Section: Number Of Effective Tillers Hill -1supporting
confidence: 92%
See 2 more Smart Citations
“…The response of difference in producing bearing tillers hill -1 might be due to the variation in genetic makeup of the variety. The above results of variability in effective tillers hill -1 are also in full agreement with many workers (Sohel et al, 2009;Hossain et al, 2005;Shrirame and Muley, 2003). The differential response of tillering in the varieties could be attributed due to its genetic potentiality.…”
Section: Number Of Effective Tillers Hill -1supporting
confidence: 92%
“…Differences in the production of total tillers hill -1 might be due to genetic variation, physiological functions and growth characters of the varieties under study. Similar trend were also found by Sohel et al (2009) who reported that all the yield and yield contributing character differed significantly due to variation of their genotypic characteristics. Razzaque et al (2009), Jeng et al (2009 and many other scientists were also found similar findings with the present study.…”
Section: Number Of Total Tillers Hill -1supporting
confidence: 86%
See 1 more Smart Citation
“…Namun dengan tersedianya prototipe caplak sebagai alat penggarisdi permukaan tanah memudahkan menanam padi dengan cara jajar legowo. Menurut Sohel et al (2009), jarak tanam optimum akan memberikan pertumbuhan yang lebih baik sehingga tanaman dapat memanfaatkan lebih banyak cahaya matahari dan unsur hara.…”
Section: (9) Peubah Dummy Sistem Tanamunclassified
“…Jajar legowo 2:1 system resulted in the highest leaf N concentration (0.22%) and the lowest was found at 25 x 25 cm planting distance system ( 0.13%). According to Sohel et al (2009), the optimum distance would provide growth in the upper part of the plant, thus it could utilise more sunlight. Moreover, it would improve root development, so it would effectively absorb nutrients.…”
Section: Plant Growth Chemical Properties and Grain Yieldmentioning
confidence: 99%